Listeria Monocytogenes Meningoencephalitis in an Immunocompromised Patient: A Diagnostic and Therapeutic Challenge - Nabih, I.; Tougar, S.; Alaoui, S.; Qasbaoui, C.; Naghir, Z.; Charra, B. (British Journal of Healthcare and Medical Research, 2025)
Neuro-meningeal listeriosis is a rare CNS infection primarily affecting immunocompromised patients. We report a 25-year-old woman with lupus nephritis on azathioprine, presenting with febrile altered consciousness, gastrointestinal symptoms, and seizures. MRI showed deep temporo-occipital hyperintensities without enhancement. Diagnosis was confirmed by positive blood cultures and CSF multiplex PCR. Treatment with ampicillin and gentamicin led to recovery. This case illustrates the diagnostic challenge of atypical presentations and underscores the importance of combining imaging and molecular diagnostics for timely management.